Enhancing Small Business Quality: Strategy Development for Classifying SMEs in Palembang - Kesuma, Nilam; Meirawati, Eka; Nurullah, Asfeni; Gozali, Efva Octavina Donata (Yumary: Jurnal Pengabdian kepada Masyarakat, 2025)
Purpose: This community service aims to provide training and develop strategies to improve the quality of small businesses based on the classification of SMEs in Palembang, South Sumatra. Methodology/approach: This research was conducted using a sample of data from 15 printing MSMEs in Palembang. The methodology follows a systematic process involving classification and association analysis. Data attributes such as Business Status, Business Classification, Place of Birth, Age, Gender, Education, Occupation, Marital Status, and Domicile were selected and transformed for analysis. The classification and association algorithms were applied to reveal the relationships between variables, using relevant categorization such as age groups (e.g., early adulthood, late adulthood, etc.). Results/findings: The findings show that by categorizing and analyzing the attributes of the MSMEs, strategies effectively enhance their income and operational efficiency. Moreover, the study found that 76% of participants successfully implemented appropriate strategies following the training. On average, businesses experienced a 15% increase in income and a 20% improvement in production efficiency. Conclusions: This training significantly contributed to improving the performance of printing MSMEs in Palembang by enhancing entrepreneurs’ understanding of business classification, operational efficiency, and targeted development strategies. It also fostered collaboration and strengthened business networks to support MSME competitiveness. Limitations: The limitation lies in the sample size, which includes only 15 printing MSMEs. This may limit the generalizability of the findings to other MSMEs in different regions or industries. Additionally, the data collected is based on self-reported information, which could introduce bias or inaccuracies in the analysis. Contribution: This study contributes to SME development by emphasizing the importance of classification-based strategies. The findings offer valuable insights for policymakers, training organizations, and SME owners in creating more targeted, effective strategies to enhance SME performance in Palembang.